Network indicators of the social ecology of adolescents in relative and non-relative Foster households. (February 2017) - Blakeslee, Jennifer; Kothari, Brianne H.; McBeath, Bowen; Sorenson, Paul; Bank, Lew
Abstract: Though the presence, composition, and quality of social relationships—particularly as found in family networks—has an important influence on adolescent well-being, little is known about the social ecology of youth in foster care. This study examined the social networks of foster youth participating in a large RCT of an intervention for siblings in foster care. Youth reported on the people they lived with and the relatives they were in contact with, which provided indicators of network size, composition, and relationship quality. Cluster analysis was used to identify five family network profiles for youth living in foster homes. Two identified subgroups reflected robust family networks where youth were living with relative caregiver(s) and related youth, and also reported multiple family ties outside the household, including with biological parents. The remaining three profiles reflected youth reports of fewer family connections within or beyond the foster household, with distinctions by whether they lived with siblings and/or reported having positive relationships with their mothers and/or fathers. The identified network profiles were validated using youth- and caregiver-reported measures of mental health functioning, with increased caregiver report of post-traumatic stress symptoms indicated for the three subgroups that were not characterized by a robust family network. Highlights: Foster youth reported on their current household composition and family networks. Cluster analysis identified family network profiles within and beyond foster homes. Two profiles reflect relative placements and robust family networks. Three profiles show fewer family connections within or beyond the foster home. Profiles showed differences in caregiver reports of post-traumatic stress symptoms.